2011
DOI: 10.1021/jp2006815
|View full text |Cite
|
Sign up to set email alerts
|

Universal Stability and Temperature Dependent Phase Transformation in Group VIIIB–IB Transition Metal FCC Nanowires

Abstract: Atomistic simulation of Ag, Al, Au, Cu, Ni, Pd, and Pt FCC metallic nanowires show a universal FCC → HCP phase transformation below a critical cross-sectional size, which is reported for the first time in this paper. The newly observed HCP structure is also confirmed from previous experimental results. Above the critical cross-sectional size, initial ⟨100⟩/{100} FCC metallic nanowires are found to be metastable. External thermal heating shows the transformation of metastable ⟨100⟩/{100} FCC nanowires into ⟨110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In recent years, many new materials of nanoparticles have been synthesized and applied in potential domains. Note that there is often phase transformation among face-centered cubic ( fcc ), body-centered cubic ( bcc ) and hexagonal closed-packed ( hcp ) systems in mono-component nanocrystal superlattices, especially for the noble metal nanostructures 1 2 3 4 5 6 7 8 9 . This can be attributed to the diffusion of guest molecules (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many new materials of nanoparticles have been synthesized and applied in potential domains. Note that there is often phase transformation among face-centered cubic ( fcc ), body-centered cubic ( bcc ) and hexagonal closed-packed ( hcp ) systems in mono-component nanocrystal superlattices, especially for the noble metal nanostructures 1 2 3 4 5 6 7 8 9 . This can be attributed to the diffusion of guest molecules (e.g.…”
mentioning
confidence: 99%
“…This can be attributed to the diffusion of guest molecules (e.g. dodecanethiol) 3 , surface stress 4 5 , specific stacking processes depending on evaporation kinetics 6 and high pressure 7 8 etc. Solid Au is usually most stable as an fcc structure.…”
mentioning
confidence: 99%
“…Hence, surface effects are dominant factors affecting the structure of nanowires and can even induce thorough structural transition. On the heels of these discoveries, other interesting materials properties such as surfaceinduced lattice reorientation, martensitic phase transformation (MT), pseudo-elastic behavior, and shape memory effects (SMEs) have been studied and observed from fcc [14,[19][20][21][22][23]28,[63][64][65][66][67][68][69][70][71][72][73][74][75], bcc [76][77][78][79][80][81][82], and hcp [83,84] single-element, layered composite [85][86][87][88][89], intermetallic alloy [90][91][92][93][94][95], and even metal oxide [96][97][98][99][100] or nitride [101] compound nanowires. The reversible strain can be as high as 40-70% and is much lar...…”
Section: Size-dependent Structural Stability Of Nanomaterialsmentioning
confidence: 99%
“…The prediction can be extended to other scenarios if the critical stress and surface stress are known. Sutrakar and Mahapatra [74] have proposed two critical wire widths l c and d c with l c < d c and three regions to distinguish the stability of fcc nanowires in the <1 0 0>/{1 0 0} configuration. When the crosssection is smaller than d c but larger than l c , the nanowire is metastable and will reorient into the <1 1 0>/{1 1 1} configuration at a temperature higher than the critical value as described above.…”
Section: Temperature and Pressure-dependent Critical Sizementioning
confidence: 99%
“…In recent past, MD simulations have been used extensively in understanding the structural and thermo-mechanical behaviors of materials at nanoscale [8][9][10][11] including effect of free surfaces on the martensitic cubic-to-tetragonal transformation in Ni-Al alloy 12 , effect of strain rate and temperature on the mechanical properties of Ni-Al nanowire 13 , asymmetry in structural and thermo-mechanical behavior of B2-NiAl nanowire under tensile and compressive loading 14 , etc. Recently, it has been observed that an initial <100> oriented B2-NiAl nanowire undergoes B2-BCT phase transformation for a given range of temperature [15][16] .…”
Section: Introductionmentioning
confidence: 99%